Modelling Data Mining Dynamic Code Attributes With Scheme Definition Technique - Evasaria M Sipayung; Cut Fiarni; Randy Tanudjaja (IAES Indonesia Section, 2014)
Data mining is a technique used in differentdisciplines to search for significant relationships among variablesin large data sets. One of the important steps on data mining isdata preparation. On these step, we need to transform complexdata with more than one attributes into representative format fordata mining algorithm. In this study, we concentrated on thedesigning a proposed system to fetch attributes from a complexdata such as product ID. Then the proposed system willdetermine the basic price of each product based on hiddenrelationships among the attributes of data. These researchesconclude that the proposed system accuracy of precision rate is98.7% and recall rate are 70.27%.